2000
DOI: 10.1007/s004120050413
|View full text |Cite
|
Sign up to set email alerts
|

A homologue of the yeast HOP1 gene is inactivated in the Arabidopsis meiotic mutant asy1

Abstract: Synapsis of homologous chromosomes is a key event in meiosis as it is essential for normal chromosome segregation and is implicated in the regulation of crossover frequency. We have previously reported the identification and cytological characterisation of a T-DNA-tagged asynaptic mutant of Arabidopsis thaliana. We have demonstrated that this mutant, asy1, is defective in meiosis in both males and females. Cloning and nucleotide sequencing of the ASY1 gene has revealed that it encodes a polypeptide of 596 amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
228
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(230 citation statements)
references
References 42 publications
2
228
0
Order By: Relevance
“…Previously, we characterized an asy1 T-DNA mutant in a Wassilewskija (Ws) genomic background (Caryl et al 2000). For this report, we have analyzed a T-DNA insertion line in a Columbia (Col-0) background.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we characterized an asy1 T-DNA mutant in a Wassilewskija (Ws) genomic background (Caryl et al 2000). For this report, we have analyzed a T-DNA insertion line in a Columbia (Col-0) background.…”
Section: Resultsmentioning
confidence: 99%
“…ASY1 is an Arabidopsis HORMA domain protein that exhibits homology within this domain with Hop1 and HIM3 (Caryl et al 2000). Immunolocalization studies have revealed that ASY1 is initially detected as numerous punctate foci in pollen mother cells (meiocytes) during G2.…”
mentioning
confidence: 99%
“…REC8 and HOP1 are conserved across diverse species, and their homologs (At-REC8/At-SYN1/At-DIF1 [three names for the same gene] and Os-REC8 for REC8; ASY1 and PAIR2 for HOP1) have also been identified in Arabidopsis and rice. Depletion of REC8 causes chromosome fragmentation and formation of univalents (Cai et al, 2003;Chelysheva et al, 2005;Shao et al, 2011), and mutation of ASY1 and PAIR2 also results in defects in synapsis and CO formation in Arabidopsis and rice, respectively (Caryl et al, 2000;Nonomura et al, 2006;SanchezMoran et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies strongly support the idea that SC is dependent on the initiation of recombination by DSBs. A mutation in the Arabidopsis ASY1 gene encoding an HOP1 homolog also causes a reduction in chiasmata number [54,55]. In addition, Arabidopsis sds mutant also shows greatly reduced frequency of meiotic recombination [20], and some other mutants defective in meiotic recombination including atspo11-1, atrand51, atxrcc3 and rck [8,30,56,57] are unable to achieve normal SC formation, indicating that normal levels of recombination are needed for proper SC formation.…”
Section: Roles Of Sds and Rck In Rice Male Meiosismentioning
confidence: 99%
“…In Arabidopsis, the ASY1 protein is localized to the axial/lateral elements and an asy1 mutant is asynaptic and unable to form SC in both male and female meiocytes, indicating its critical role in SC formation [54,58,62]. A mutation in PAIR2, the rice homolog of ASY1, causes defects in homolog alignment at pachytene and the formation of univalents instead of bivalents at diakinesis [63].…”
Section: Conserved Male Meiosis In Monocots and Eudicotsmentioning
confidence: 99%